2013
DOI: 10.1200/jco.2012.48.5516
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic DNA Methylation Signature for Stage I Non–Small-Cell Lung Cancer

Abstract: A B S T R A C T PurposeNon-small-cell lung cancer (NSCLC) is a tumor in which only small improvements in clinical outcome have been achieved. The issue is critical for stage I patients for whom there are no available biomarkers that indicate which high-risk patients should receive adjuvant chemotherapy. We aimed to find DNA methylation markers that could be helpful in this regard. Patients and MethodsA DNA methylation microarray that analyzes 450,000 CpG sites was used to study tumoral DNA obtained from 444 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
220
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 254 publications
(230 citation statements)
references
References 39 publications
8
220
1
1
Order By: Relevance
“…Advancement in high-throughput methodologies and their application in molecular and genetic epidemiological studies have expanded the potential for "omic"-based risk prediction (41). Genome-wide association studies have identified inherited susceptibility patterns for lung cancer at different loci (42)(43)(44), and several methylation (45)(46)(47) and microRNA biomarkers (48-51) associated with lung cancer have been identified. It is anticipated that many more DNA polymorphism and biomarkers will be developed.…”
Section: Discussionmentioning
confidence: 99%
“…Advancement in high-throughput methodologies and their application in molecular and genetic epidemiological studies have expanded the potential for "omic"-based risk prediction (41). Genome-wide association studies have identified inherited susceptibility patterns for lung cancer at different loci (42)(43)(44), and several methylation (45)(46)(47) and microRNA biomarkers (48-51) associated with lung cancer have been identified. It is anticipated that many more DNA polymorphism and biomarkers will be developed.…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation, which involves the enzymatic addition of a methyl group to the fifth position of the deoxycytidine residue in each affected CpG dinucleotide (6,7,9), leads to chromatin remodeling. This results in gene silencing and has been associated with cancer development through the inactivation of tumor suppressor genes (10)(11)(12)(13)(14)(15)(16). Unlike DNA sequence alterations, epigenetic modifications, such as DNA methylation, are dynamic and reversible with proven therapeutic implications (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, methylation may hold promise as an 'at diagnosis' biomarker of long-term tumor outcome, similar to that described in colorectal, breast and lung cancers. [52][53][54] Although many of the novel genes we identified have not been previously reported in bladder cancer, their inappropriate methylation, accompanied with gene-silencing, has been reported in the context of other tumor types and suggests potential roles as tumor suppressor genes. 55,56,57 To determine associations between methylation and gene expression, we confined our studies to genes showing frequent and/or high mean levels of methylation.…”
Section: Discussionmentioning
confidence: 95%